Keautentikan Kisah Nabi Saleh dan Kaum Samud dalam Tafsir Ilmi Kemenag (Perspektif Historis Teologis) - Husni Wijaya; Masykuroh, Siti; Hendro, Beko (Institut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2024)
This study aims to examine the authenticity of the story of Prophet Saleh and the Thamud people as presented in the Tafsir Ilmi by the Ministry of Religious Affairs (Kemenag), to determine whether the story is historically accurate or merely a legend. Traditionally, stories of prophets and messengers are largely accepted based on faith, while the advancement of science provides historical data documented by historians. By utilizing a historical approach based on information from the Qur'an and findings from scholars and archaeologists, this research seeks to assess the validity of the narrative. This study employs a qualitative method with a library research technique and descriptive analysis. The findings indicate that the story of Prophet Saleh and the Thamud people in the Tafsir Ilmi by Kemenag is considered authentic. The research reveals a consistent genealogy of Prophet Saleh as documented in the Tafsir Ilmi by Kemenag and Tafsir Ath-Thabari, corroborated by genealogical references in the Bible. This suggests that Prophet Saleh descended from Prophet Noah through his son, Sam. Additionally, there is alignment between the perspectives of Tafsir Ilmi by Kemenag, Tafsir Ath-Thabari, and Tafsir Qurthubi, supported by prophetic hadiths and the Bible regarding the location of the Thamud civilization. This location is identified as a mountainous region in Saudi Arabia, situated between the city of Medina and the Levant (Syria, Lebanon, Jordan), presently known as Madain Saleh—a settlement of the descendants of the Thamud people, namely the Nabateans, who were spared from Allah's punishment